(untitled) (ACME, 2021)
Historian with multiple interests, librarian, musician, man of culture and great modernist, scholar, in particular, of Eighteenth-Century Italy, Calogero Farinella prematurely left us in June 2019, at just over sixty years old. His publications on eighteenth-century Genoa and Enlightenment science (Verona especially: Francesco Bianchini, Anton Mario Lorgna and the Accademia dei Quaranta) make and will always give in the studies of history of culture. A student of salvatore Rotta (1926-2001), from whom he muttered his passion for the 18th century in particular, Farinella graduated under his guidance on William Godwin (1756-1836), father of Mary Shelley, radical philosopher and political writer of the libertarian area, who, with his fundamental work, marks the passage, in Britain, from the Enlightenment to Romanticism. On Godwin’s figure and writings, obtaining them from his dissertation of his degree, Farinella extracted and published in the Eighties of the last century two articles, appeared in the volume of the Miscellanea storica ligure containing many studies in honor of the Professor Francesco Cataluccio (William Godwin ed il suo Journal all’epoca della Rivoluzione Francese, xv, 1984) and later on Studi settecenteschi (Il governo più semplice. Il mito democratico-repubblicano in William Godwin, viii, 1987). A third article, which contains really interesting ideas about Godwin’s utopian novel, remained unpublished, to this day, despite the objective and relevant value of Farinella’s contribution. We therefore believe that we are doing something that is pleasing to the memory of our friend and scholar by publishing it here for the first time.